A case study of syntactic patterns of Egyptian Colloquial Arabic-English code-switching - Farid, Salma Mohamed (AUC Knowledge Fountain, 2019)
The present study investigated the structural patterns of Egyptian Colloquial Arabic (ECA)-English code-switching in the domains of classroom and interviews at the American University in Cairo (AUC) by applying Pieter Muysken's typology of code-mixing and relating it to the work of Poplack (1980) and Myers-Scotton (1993). It also aimed to stand on the nature of inflectional derivational and close-classed morphemes affixed to code-switched lexical items. The nature of the study was descriptive exploratory in which textual linguistic analysis was employed to analyze audio-recorded verbal data. The data was collected by observing four undergraduate classrooms held by the Department of English Language Instruction at AUC and conducting three focus group interviews with AUC graduate students. The results indicated that insertion pattern was more frequent in both domains, followed by alternation and congruent lexicalization (CL), which occurred more frequently in the interview domain. The results also showed that ECA definite article il- was utilized with English nouns in the insertion and CL patterns in both domains. While verb inflections were affixed to ECA verbs in classroom domain and to English verbs in the interview domain. The results indicated the use of English as the matrix language in classroom domain and the variation of the matrix language between ECA and English in the interview domain.